Zagros studies: proceedings of the NINO Jubilee Conference and other research on the Zagros region - Eidem, J. (PIHANS, 2020)
La 4e de couverture indique : "Zagros Studies contains nine articles on the archaeology and history of the Zagros Region in Iraq. Five of these are expanded versions of papers that were delivered at a conference celebrating the 75th anniversary of The Netherlands Institute for the Near East (NINO) in December 2014. The other articles present results of the NINO archaeological project on the Rania Plain, and new investigations on the Shemshara Hills and other sites on the plain, which are threatened by Lake Dokan ; a spectacular terracotta "tower" is published here for the first time."
Literaturangaben
5 contributions sont issues du "NINO Jubilee meeting Zagros" organisé en décembre 2014 pour célébrer les 75 ans de "The Netherlands Institute for the Near East (NINO)"
Keywords: Konferenzschrift -- 12.2014 -- Leiden; Vor- und Frühgeschichte; Archäologische Stätte; Kulturkontakt; Zagrosgebirge